Online-Based Promotion Strategy Implementation On Cv Auto Mobil Inti Jaya - Edy Yulianto Putra; Jessy Jessy (ConCEPt - Conference on Community Engagement Project, 2023)
CV Auto Mobil Inti Jaya is a company engaged in buying and selling vehicles, but CV Auto Mobil Inti Jaya does not have any system nor understanding for marketing and advertising through social media. This was the beginning of the practical work activities carried out to help CV Auto Mobil Inti Jaya to be able to design and apply an online or social media-based marketing system into their work system. The data collection method used is the interview method, the observation method and also the documentation method. The result of the practical work that has been carried out is the design of an online-based marketing system that can be used directly by CV Auto Mobil Inti Jaya with their social media. May the suggestions and conclusions that have been summarized can help similar research in the future.